Reflections on the Difficulties that the Development and Progress of Organic Metallic Chemistry have in Colombia - Galarza, Esperanza (Revista de Ciencias, 2014)
This paper discusses the relatively slow development of research on organometallic chemistry in Colombia compared to that in the world, based on funded projects and publications, as well as, government and educational issues. This paper also discusses the need to promote developments in this area, highlighting the importance of basic scientific research. Its aim is to motivate peers to lead educational processes and research through networking, collaboration and cooperation programs at the national and international level.